Incremental Current Based MPPT for a PMSG Micro Wind Turbine in a Grid-Connected DC Microgrid. (December 2017) - Zammit, Daniel; Staines, Cyril Spiteri; Micallef, Alexander; Apap, Maurice; Licari, John
Abstract: This paper presents an incremental-type current based Maximum Power Point Tracking (MPPT) system for a micro wind turbine (MWT) connected to a DC microgrid under grid-connected operation. The system consists of a Permanent Magnet Synchronous Generator (PMSG) driven by a MWT which is interfaced to the DC microgrid through a rectification stage and a boost converter. The proposed MPPT system provides a reference current for a Proportional Integral (PI) current controller which controls the inductor current in the boost converter connecting the system to the DC microgrid. The reference current produced by the MPPT system varies according to the DC link voltage to obtain maximum power transfer to the DC microgrid at all wind speeds. The MPPT system, the boost converter and current control are explained in detail. Simulation results of the system operating under varying wind conditions are presented to highlight the performance of the developed MPPT algorithm.